Assessment of the agronomic value of solar-dried sludge and heavy metals bioavailability based on the bioaccumulation factor and translocation index - An-nori, Amal; El Mejahed, Khalil; Fels, Loubna El; Touhami, Driss; Ezzariai, Amine; El Gharous, Mohamed; Hafidi, Mohamed (Frontiers in Environmental Science, 2023)
This study aimed to assess the agronomic value of solar dried sludge (SDS) and the transfer of Cr, Ni, Pb and Cu to wheat (Triticum aestivum) and faba bean (Vicia faba). A greenhouse experiments were performed involving two rates of SDS previously sampled from an activated sludge based WWTP (15 t/ha and 30 t/ha). Additionally to the single use of SDS amendment, co-application of SDS and mineral fertilizers was engaged to judge the best scenario leading for important yields and less negative implications on the environment. For both wheat and faba bean, data showed that the applied SDS at 30t/ha led to competitive yields compared to the ones obtained while 15 t/ha of SDS and mineral fertilizers were co-applied. The use of SDS increased soil organic matter, decreased slightly the pH and increased soil salinity. The contents of Ni, Cu and Pb were not significantly affected by the application of SDS. Only Cr showed important concentrations in soil proportionally to the increasing rates of SDS. The bioaccumulation of heavy metals in roots was more important in 30t/ha than 15 t/ha amended soil. In the case of wheat, the BCF roots values correspond to the following order: Cr (0.89) >Cu (0.85)> Ni (0.28)> Pb (0.22). In the case of faba bean, BCF roots were found as following: Cu (1.04> Ni (0.37)> Cr (0.16)> Pb (0.15). Wheat excluded Cr, Ni and Pb from the uptake by shoots and Cu was translocated from roots to shoots with a percentage of 11% at 30t/ha of applied SDS. Faba bean demonstrated more important values of HMs translocation respecting this order (Ni (37.7%) > cu (30.24%)> Cr (17.59%) while Pb was excluded from the translocation. No significant difference was noticed regarding the translocation index when sludge rate has been duplicated from 15 t/ha to 30 t/ha. Based on these outcomes, SDS use at 30t/ha rate is the best scenario to amend the soil and to provide nutrient to plants. Wheat is less translocating for heavy metals to the edible part; it is thus the most suitable crop to be involved in the current context.